2006
DOI: 10.1136/qshc.2005.017095
|View full text |Cite
|
Sign up to set email alerts
|

Reduced morbidity for elderly patients with a hip fracture after implementation of a perioperative evidence-based clinical pathway

Abstract: Implementation of an evidence based clinical pathway reduced postoperative morbidity and did not affect in-hospital mortality or overall costs of inpatient care. The effect of changing trends in medical care cannot be ruled out, but the reduction in complications in several clinical areas lends support to the positive impact of the clinical pathway. Perioperative CP is one successful management approach for this fragile patient population as patient morbidity was reduced without negatively affecting resource u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 32 publications
0
76
1
3
Order By: Relevance
“…Postoperative pneumonia rate did not show any improvement, which was similar to other studies. 11,14,15 We achieved excellent clinical outcomes in the past 5 years in terms of short-term mortality rate. The 30-day mortality rate in our study was generally much lower than the commonly quoted figures, ranging from 5.1% to 13%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Postoperative pneumonia rate did not show any improvement, which was similar to other studies. 11,14,15 We achieved excellent clinical outcomes in the past 5 years in terms of short-term mortality rate. The 30-day mortality rate in our study was generally much lower than the commonly quoted figures, ranging from 5.1% to 13%.…”
Section: Discussionmentioning
confidence: 93%
“…More and more evidences showed that these osteoporotic fractures should be managed with aggressive medical and surgical support, which achieved excellent results with good clinical outcomes. 13 One of the uniqueness of our clinical pathway when comparing with the other pathways in the world [9][10][11]14,15 is that ours starts from the emergency department of the acute hospital when the patient is admitted and continues all the way to another rehabilitation hospital until the patient is discharged home. This ensures a smooth running of the whole chain of care.…”
Section: Discussionmentioning
confidence: 99%
“…As the addition of a trauma room has been shown to dramatically decrease the volume of overnight surgeries and complications, and as the institution of a hip fracture pathway for medical management has been shown to decrease perioperative morbidity, their results might not demonstrate as clear an effect of DTG versus NTG hip fracture repair. [42][43][44][45] In our cohort, institution of a hip fracture pathway as well as provision of a dedicated trauma room occurred prior to data collection, thus eliminating these factors as confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…This model of care has previously been shown to decrease length of stay (LOS), re-admission rates, complications, costs of care, and in-hospital mortality. 25,[31][32][33][34][35][36] …”
mentioning
confidence: 99%